Dental Opioid Prescribing and Multiple Opioid Prescriptions Among Dental Patients: Administrative data from the South Carolina Prescription Drug Monitoring Program - McCauley, Jenna L. (J Am Dent Assoc, 2016)
BACKGROUND: Despite increased attention to dentists’ role in curbing opioid misuse, abuse, and diversion, information regarding prescribing practices and the frequency of multiple concurrent opioid prescriptions among dental patients is limited. METHODS: Prescription drug monitoring program (PDMP) data for South Carolina representing dispensed medication for patients prescribed at least one opioid by a dentist over the most recently available two-year frame (2012–2013) was reviewed. Descriptive analyses examined: (1) types, frequency of dental opioid prescriptions; and, (2) frequency of existing multiple concurrent opioid prescriptions among dental patients. RESULTS: Nearly all dispensed dental opioid prescriptions (99.9%; n = 653,650) were for immediate release opioids and were initial fills (96.2%). Hydrocodone (76.1%) and oxycodone (12.2%) combination products were the most frequently dispensed opioids prescribed by dentists. Individuals under 21 years of age received 11.2% of dentist prescribed opioids dispensed. Patients with multiple concurrent opioid prescriptions were identified within 30-day (n=113,818), 90-day (n=166,124), and 180-day (n=205,576) timeframes. CONCLUSIONS: Dentists prescribed a high volume of immediate release opioids dispensed in South Carolina. A notable minority of dental patients had incident(s) of multiple pre-existing opioid prescriptions, a factor implicated in patient misuse, abuse, overdose, and diversion PRACTICAL IMPLICATIONS: Use of a PDMP prior to prescribing provides a record of controlled substances dispensed to a patient, and may inform prescribing, coordination of care, and addiction screening or referral. Patients should be provided information regarding misuse behaviors and their risks, as well as the importance of secure storage and disposal of leftover opioid medications.